ADAMTS and ADAM metalloproteinases in osteoarthritis - looking beyond the ‘usual suspects’ - Yang, C; Chanalaris, A; Troeberg, L (Elsevier, 2017)
Introduction Matrix metalloproteinases and ‘aggrecanase’ ADAMTSs are well established to play key roles in osteoarthritis (OA) through degradation of extracellular matrix type II collagen and aggrecan, and are thus potential targets for development of OA therapies. Objectives This paper aims to provide a comprehensive review of the expression and potential roles of other, lesser-known ADAMTSs and related adamalysins (or ADAMs) in cartilage, with a view to identifying potentially protective or homeostatic metalloproteinases in the joint and informing consequent selective inhibitor design. Design A comprehensive literature search was performed using PubMed terms ‘osteoarthritis’ and ‘ADAMTS’ or ‘ADAM’. Results Several ADAMTSs and ADAMs were identified as having reportedly increased expression in OA. These include enzymes likely to play roles in cartilage matrix anabolism (e. g. the procollagen N-proteinases ADAMTS-2, ADAMTS-3 and ADAMTS-14), chondrocyte differentiation and proliferation (e. g. ADAM9, ADAM10, ADAM12), as well as enzymes contributing to cartilage catabolism (e. g. COMP-degrading ADAMTS-7 and ADAMTS-12). Conclusion In addition to the well-characterised MMPs, ADAMTS-4 and ADAMTS-5, many other ADAMTSs and ADAMs are expressed in cartilage and several show significantly altered expression in OA. Studies aimed at elucidating the pathophysiological roles of these enzymes in cartilage will contribute to our understanding of OA pathogenesis and enable design of targeted inhibitors that effectively target metalloproteinase-mediated cartilage degradation while sparing cartilage repair pathways.